Answer:
Step-by-step explanation:
Given,
![f(x)=-x^{2} +6x-1\\g(x)=3x^{2} -4x-1](https://tex.z-dn.net/?f=f%28x%29%3D-x%5E%7B2%7D%20%2B6x-1%5C%5Cg%28x%29%3D3x%5E%7B2%7D%20-4x-1)
we know,
(f-g)(x)=f(x)-g(x)
So, here we get
(f-g)(x)
=f(x)-g(x)
=![-x^{2} +6x-1-(3x^{2} -4x-1)](https://tex.z-dn.net/?f=-x%5E%7B2%7D%20%2B6x-1-%283x%5E%7B2%7D%20-4x-1%29)
=![-x^{2} +6x-1-3x^{2} +4x+1](https://tex.z-dn.net/?f=-x%5E%7B2%7D%20%2B6x-1-3x%5E%7B2%7D%20%2B4x%2B1)
=![-x^{2}-3x^{2} +6x+4x-1+1](https://tex.z-dn.net/?f=-x%5E%7B2%7D-3x%5E%7B2%7D%20%2B6x%2B4x-1%2B1)
=![-4x^{2} +10x](https://tex.z-dn.net/?f=-4x%5E%7B2%7D%20%2B10x)
So, the answer is
![-4x^{2} +10x](https://tex.z-dn.net/?f=-4x%5E%7B2%7D%20%2B10x)
Answer:
o.2222
Step-by-step explanation:
just divide one by five
hope that helps
Answer:8.56
Step-by-step explanation:
Answer:
1) and 3)
Step-by-step explanation:
Well it all depends on the object you are using but in this case lets say remote control cars. You can have an example like "we drove the car around the building twice. the first time it was -8 than how fast it was supposed to go. the second time it was 9. In which round was the car faster?" I dont think i helped very much but i hope i did